The Impact of Sports Participation on Oral Health: A Comprehensive Review - Nosowicz, Konstancja; Różak, Patrycja; Draguła, Michał; Musielińska, Marcelina; Malicka, Patrycja; Wójcik, Joanna (Quality in Sport, 2026)
Purpose: To analyze the bidirectional relationship between sports participation and oral health, evaluating the physiological, nutritional, and mechanical challenges on the stomatognathic system and their impact on athletic performance. Materials and Methods: A review of 25 peer-reviewed studies (2005–2026) evaluated four domains: (1) sports nutrition's effects on dental tissues; (2) oral inflammation's impact on recovery; (3) traumatic dental injuries (TDIs) and mouthguard efficacy; and (4) exertion-induced biomechanical stress (bruxism, temporomandibular disorders). Results: Athletes face a disproportionately high prevalence of oral diseases. Sports diets cause up to 84% caries and 59% erosion rates. Unmanaged periodontal inflammation delays muscle recovery by generating systemic inflammation. Custom mouthguards prevent TDIs without compromising respiratory parameters (e.g., VO2 max), yet compliance is alarmingly low. Furthermore, over 60% of athletes in specific disciplines exhibit exertion-induced clenching, linking high-intensity sports to awake bruxism and severe tooth wear. Conclusions: Athletic activity imposes severe oral health challenges through erosive diets, high-velocity trauma, and biomechanical stress. Because poor oral health impairs athletic output, integrating sports dentistry into standard medical care is vital. Routine screenings, preventive protocols, and mandatory custom mouthguards are essential to protect athletes' health and competitive careers.